1998
DOI: 10.1104/pp.116.2.617
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Regulation of Somatic Embryogenesis by Adjusting Cellular Polyamine Content in Eggplant1

Abstract: Four critical stages of embryogenesis, including callus induction, cellular acquisition of morphogenetic competence, expression of embryogenic program, and development and maturation of somatic embryos during somatic embryogenesis from leaf discs of eggplant (Solanum melongena L.), were identified by scanning electron microscopy. Temporal changes in arginine decarboxylase (ADC) activity and polyamines (PAs) during critical stages of embryogenesis revealed that high levels of PAs (especially putrescine [PUT]), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 36 publications
3
8
0
1
Order By: Relevance
“…Results shown here are a new evidence of the crucial role that free polyamines play in somatic embryogenesis in various plant systems, as previously reported (Minocha and Minocha 1995;Yadav and Rajam 1998;Silveira et al 2006). Nevertheless, recent studies have shown the involvement of conjugated (Santa-Catarina et al 2007) and bound (De-la-Peña et al 2008) PAs in early stages of somatic embryo development in Ocotea catharinensis and Coffea canephora, respectively.…”
Section: Polyamines Contentsupporting
confidence: 70%
See 1 more Smart Citation
“…Results shown here are a new evidence of the crucial role that free polyamines play in somatic embryogenesis in various plant systems, as previously reported (Minocha and Minocha 1995;Yadav and Rajam 1998;Silveira et al 2006). Nevertheless, recent studies have shown the involvement of conjugated (Santa-Catarina et al 2007) and bound (De-la-Peña et al 2008) PAs in early stages of somatic embryo development in Ocotea catharinensis and Coffea canephora, respectively.…”
Section: Polyamines Contentsupporting
confidence: 70%
“…In addition, polyamines have been studied in relation to somatic embryogenesis in many plant systems (Nieves et al 2003;Minocha et al 2004;Bertoldi et al 2004, Silveira et al 2006Santa-Catarina et al 2007) and some reports show PAs involvement in this process, particularly in their free form (Minocha and Minocha 1995;Yadav and Rajam 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Bertoldi et al (2004) in Vitis vinifera and Bastola and Minocha (1995) in carrot have shown that a positive correlation exists between SE and enhanced ODC activity. Yadav and Rajam (1998) have reported that on account of high activity of ADC (the other enzyme involved in Put synthesis) during induction of embryogenic callus of leaf discs of eggplant, there were high titers of free Put as compared to Spd and Spm. But, immunoassays using antibodies have shown increased ADC levels corresponding to embryo maturation and not embryo induction (Amarasinghe et al 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Very little is known about the underlying mechanisms that may regulate morphogenesis in addition to plant growth regulator effects (Yadav and Rajam 1998). PAs have been shown to be important for cellular differentiation to SE (Chi et al 1994;Bajaj and Rajam 1996;Rajam 1997) and have been suggested as regulators of SE (Montague et al 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation